A Case Report on the Management of Asthikshaya (Nutritional Rickets) by Ayurveda and Yoga (AYUSHDHARA, 2024)
Rickets is a disorder of growing bone due to abnormal mineralisation of bone. It affects longer bones, leading to poor bone growth and bony deformities such as bow legs and knock-knees in children. No direct description of such disease has been found in Ayurveda; the clinical manifestations due to Asthikshaya (deficient bony tissue) can be considered as rickets. Despite conventional treatment of supplementation of deficient nutrients, many children do not show satisfactory response to the treatment. This is a case report of nutritional rickets in a 3.5-year-old boy who presented with leg pain, cramps and frequent falls due to knocking of knees for the last four months. He was treated with the combined principles of Ayurveda and Yoga. The patient was treated with oral drugs like Ashwagandhadi Churna, Kukkutandatwaka Bhasma, Godanti Bhasma, Muktashukti Bhasma, Lakshadi guggulu, Gandha Tail, Tiktaksheer Basti (medicated enema), Sthanika Snehan-Swedana (local oleation and sudation), Gatravestana (bandaging), knee braces, and practice of Yogasana like Tadasana (standing pose), Vrikshasana (tree pose), Utkatasana (chair pose), and Bhadrasana (butterfly pose). The symptoms were relieved, the biochemical parameters were improved and no further bending of lower limbs was observed. Thus, the patient of nutritional rickets was treated with Ayurveda and Yoga.